Determination of ceramic flaw populations from component strengths. Issue 8 (5th February 2019) - Cook, Robert F.; DelRio, Frank W.
Abstract: A procedure is outlined for determining the population of flaws in manufactured ceramics from strength measurements of sampled components. The broad applicability of the procedure is demonstrated in a quantitative manner, using strength measurements from a range of ceramic materials (eg, glass, glass‐ceramic, single crystal, and polycrystal) with different flaw types (eg, bulk, surface, and edge). The deconvoluted flaw populations are mostly dominated by small flaws with extended large flaw tails and are all in domains of tens of micrometers. The procedure greatly extends the useful information to be gained by ceramics manufacturers and designers from strength distribution measurements and emphasizes the importance of identifying strength‐limiting characteristics within a flaw population.